Losses and Abandonments in Clara Obligado’s Una casa lejos de casa. La escritura extranjera - Regazzoni, Susanna (Oltreoceano - Rivista sulle migrazioni, 2024)
This article studies the theme of exile in the book of the Argentine writer based in Spain, Clara Obligado, Una casa lejos de casa. La escritura extranjera (2020). The written reflects on life in transit, without a precise location. Argentina and Spain are two countries that share the same language that can be, at the same time, very different. Learning to use two similar and, at the same time, dissimilar languages is the challenge faced by the author whose existence takes place in a kind of non-place, in a precarious condition. The essay recounts this problematic space, in a clear challenge to political positions that are nourished by discrimination. Spain was the country chosen by many Argentinians who left their land during the last 45 years. There were several reasons; the common language, the ease of access, the Spanish ancestors of the young people stalked by their political ideas. Among the many difficulties involved in settling in another land, we must highlight the work involved in the desire to avoid contamination of the language or, as often happens, accepting a mixed result that ends up being neither Spanish nor Argentine or being the two at a time. This new literature that has emerged in Spain for decades, the result of the exile and diaspora of many non-Spanish artists by birth, is defined in different ways; For some critics, it presents hybrid characteristics (Canclini 1990), transcultural (González Dopazo 2009), extraterritorial (Noguerol 2008), or it is a deterritorialized literature (Guerrero 2012), or of the border (Noguerol 2019). Various labels that indicate diverse characteristics that point to a literary panorama in motion that destabilizes classic categories.